Video analysis in Design-Based Research – Findings of a project on self-organised learning at a vocational school - Gössling, Bernd; Daniel, Desiree (EDeR. Educational Design Research)
The use of video analysis in Design-Based Research (DBR) seems to be promising, because the quality of video data matches the reality of educational fields. Educational fields are multidimensional and complex. And more than other types of data, video may capture, for example, the simultaneity of verbal and non-verbal interactions. This seems to be valuable in the quest for new insights and better designs of educational interventions. However, to date there has been limited use of video data in researching their design. This paper aims at reflecting how the benefits of video-based analysis may be utilised in DBR. Experiences with the collection and analysis of video data in a project to design self-organised learning (SOL) at a vocational school in Germany will be used as a case study to illustrate the type of findings that may feed into the DBR process. In this case, the project school had already introduced a sophisticated SOL model but was experiencing various implementation difficulties. Resolving issues like this requires insights into how exactly a concept is realised and what happens in the field. Therefore, video data on classroom interactions was gathered and sub-sequently analysed using the documentary method. This led to the reconstruction of two different types of orientation that were guiding the students when they dealt with their self-organised learning environment. In a subversive orientation, students playfully infiltrate the formal learning space with peer activities. In a confirming orientation, students stick to both, the (informal) rules of the (formal) learning arrangement and of the peer environment, thus expressing respect for the boundary between these two worlds. These findings have been used to redesign the SOL intervention.
Keywords: Pulmonary and Respiratory Medicine; Pediatrics; Perinatology and Child Health

Open Educational Resources- Nicht nur nutzen, sondern auch erstellen! Chancen und Potenziale für die deutsche Berufsbildungslandschaft - Beutner, Marc; Schneider, Jennifer Nicole (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Überlegungen auf dem Weg zu einer Theorie lehrbezogenen Wandels an Hochschulen - Jenert, Tobias (Zeitschrift für Hochschulentwicklung)

Studien- und Lehrentwicklung als Überwindung institutioneller Grenzziehungen. Eine Netzwerktheoretische Betrachtung. - Jenert, Tobias; Sänger, Niklas (LERNEN im Hochschulzusammenhang)

Die Rolle von sozialen Netzwerken für die Lehrentwicklung und Lehrinnovation an Hochschulen - Sänger, Niklas

Digitale Transformation – Rezeption aus Sicht der Akteure in der Fachschule am Berufskolleg - Kremer, H.-Hugo; Rüsing, Peter (berufsbildung Zeitschrift für Theorie-Praxis-Dialog)

Praxissemester und Professionalisierung - Überlegungen zur Gestaltung einer universitären Begleitkonzeption - Kremer, H.-Hugo (Berufsbildung zwischen Tradition und Moderne)

Wie unterrichten wir Wirtschaft? Förderung fachbezogener Reflexion angehender Wirtschaftslehrender - Jenert, Tobias

Fachbezogene Reflexion in der beruflichen Lehrer*innenbildung - Jenert, Tobias; Brahm, Taiga; Naeve-Stoß, Nicole (bwpat)

Untangling Faculty Misinformation From an Educational Perspective: Rejoinder to ''The Menace of Misinformation: Faculty Misstatements in Management Education and Their Consequences'' - Jenert, Tobias; Brahm , Taiga (Journal of Management Education)

Theorie und Praxis der Hochschulbildungsforschung

Entwicklungsförderliche Gestaltung von Qualifizierungsbausteinen in der dualisierten Ausbildungsvorbereitung - Kremer, H.-Hugo; Frehe-Halliwell, Petra (BWP)

Eine Analyse ausbildungsvorbereitender Bildungsgänge - Kremer, H.-Hugo; Frehe-Halliwell, Petra (Potenzialorientierte Förderung in den Fachdidaktiken)

Fostering pre-service economics teachers´ reflection on their attitudes towards the discipline - Jenert, Tobias; Brahm , Taiga

Geschäftsmodell- und Kompetenzentwicklung für nachhaltiges Wirtschaften. Selbstlernmaterial für Ausbildungspersonal und Auszubildende. Bonn - Kiepe, Karina; Wicke, Carolin; Reichel, Juliane; Schlömer, Tobias; BeckerHeike, Clarissa; Jahncke, Heike; Rebmann, Karin

Geschäftsmodell- und Kompetenzentwicklung für nachhaltiges Wirtschaften. Selbstlernmaterial für Ausbildungspersonal und Auszubildende - Wicke, Carolin; Kiepe, Karina; Reichel, Juliane; Becker, Clarissa; Jahnke, Heike; Rebmann, Karin; Schlömer, Tobias

Geschäftsmodelle und Wertschöpfungsprozesse für nachhaltiges Wirtschaften – Lerngegenstände einer wirtschaftsberuflichen Bildung im Spannungsfeld von Betriebswirtschaftslehre und Wirtschaftsdidaktik - Wicke, Carolin; Kiepe, Karina; Schlömer, Tobias (bwp@ Berufs- und Wirtschaftspädagogik – online)

Das didaktisch-methodische und professionelle Selbstverständnis von betrieblichem Ausbildungspersonal im Bereich des nachhaltigen Wirtschaftens - Schlömer, Tobias; Berding, Florian; Jahnke, Heike; Becker, Clarissa; Kiepe, Karina; Wicke, Carolin; Rebmann, Karin (Zeitschrift für Berufs- und Wirtschaftspädagogik)

Zweifel am Studium? - Beratungskonzepte in der Studieneingangsphase zur Unterstützung bei individuellen Problemlagen - Kremer, H.-Hugo; Mauer, Eileen; Sloane, Hannah (bwp@ Berufs- und Wirtschaftspädagogik)

Anschlüsse eröffnen, Entwicklungen ermöglichen. Qualifizierungsbausteine inklusiv in einer dualisierten Ausbildungsvorbereitung. Reflexionen und Ergebnisse aus dem Forschungs- und Entwicklungsprojekt QBi